Flow versus pressure in the control of renin release in conscious dogs - Nafz, Benno; Berthold, Heike; Ehmke, Heimo; Hackenthal, Eberhard; Kirchheim, Hartmut; Persson, Pontus B. (American journal of physiology. Renal physiology, 1997)
In Goldblatt hypertension, renal artery stenosis reduces renal arterial pressure (RAP) and renal blood flow (RBF) and thereby increases plasma renin activity (PRA) levels. Although it is clear that reduction in RAP stimulates renin, the decrease in RBF may contribute to higher PRA as well. However, it has hitherto never been possible to dissociate a decrease in RBF from a concomitant decrease in RAP. To overcome this restriction, we used two protocols. 1) RAP was reduced in a single step to 70 +/- 0.2 mmHg (N = 8). RBF followed the sudden fall in RAP within 15 s but subsequently took on initial levels. In contrast, renal venous PRA increased from 0.95 +/- 0.22 to 5.6 +/- 1.4 ng angiotensin I.ml-1.h-1 (P < 0.05) and remained at higher values even after RBF had regained control conditions. 2) Resonance between RAP and RBF was induced by superimposing slow sinusoidal RAP waves with a period length of 450 s (N = 9), leading to a phase shift of roughly 180 degrees (time delay, 241 +/- 12 s), i.e., RBF was maximal at minimal RAP. Under these conditions, renin release was only dependent on decrements in RAP (delay of only 27 +/- 8 s). In conclusion, RBF played no major role in renin release.